Dissipativity analysis for discrete singular systems with time-varying delay. (September 2016) - Feng, Zhiguang; Li, Wenxing; Lam, James
Abstract: In this paper, the issue of dissipativity analysis for discrete singular systems with time-varying delay is investigated. By using a recently developed inequality, which is less conservative than the Jensen inequality, and the improved reciprocally convex combination approach, sufficient criteria are established to guarantee the admissibility and dissipativity of the considered system. Moreover, H ∞ performance characterization and passivity analysis are carried out. Numerical examples are presented to illustrate the effectiveness of the proposed method. Abstract : Highlights: The dissipativity analysis for discrete singular systems with time-varying delay is investigated. The results address H ∞ performance, passivity and ( Q, S, R ) - α -dissipativity in a unified framework. The results are less conservative compared with existing ones.